Efektivitas Metode Role Playing untuk Meningkatkan Pemahaman Konteks Sejarah pada Siswa Kelas V SD - Gita Cahya S; Ibnu Muthi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to examine the effectiveness of the role playing method in improving understanding of historical context in fifth grade elementary school students. The background of this study is the low ability of students to understand history as a whole, where learning tends to focus on memorizing facts such as names of figures, dates, and events, without understanding the background, process, and values ​​contained therein. The role playing method was chosen because it is able to present an active, participatory learning experience, and facilitate students to understand historical events through role simulation and story reconstruction. This study uses a qualitative approach based on literature studies, by reviewing various research results, journals, and scientific references related to the application of role playing in history learning. The results of the study show that the role playing method is effective in increasing student involvement, motivating learning, and deepening contextual understanding of historical events. In addition, role playing also contributes to developing students' social, communication, empathy, and critical thinking skills. Supporting factors for the success of this method include relevant scenario design, the role of the teacher as a facilitator, a conducive learning environment, and appropriate assessment. Obstacles such as student shyness, time constraints, and lack of facilities can be overcome with the right approach. Thus, role playing is recommended as an innovative learning strategy to improve more contextual, meaningful, and enjoyable understanding of history in Elementary Schools.